Invitro antifungal activity of some biocontrol fungi against jute pathogen Macrophomina phaseolina - A.K. BANDOPADHYAY*; N. SAMAJPATI, ANURADHA BANDOPADHYAY, (Indian Phytopathology, 2008)
Present study investigated the antagonistic potential of volatile and non-volatile components of metabolite produced by 8 selected fungal biocontrol agents (BCAs). Among the BCAs local isolates of Trichoderma viride, Gliocladium virens, Aspergillus niger and A. fumigatus were most efficient against highly virulent pathotype R9 of Macrophomina phaseolina causing cortical stem and root rot diseases in jute. Nonvolatile components isolated from T. viride JPT1, G. virens JPG1, Gliocladium sp. JPG4 and Aspergillus niger AN15 and AN27, and Aspergillus sp. A26 isolates proved to be effective in inhibiting mycelial and sclerotial growth of M. phaseolina. Experiment to evaluate the effect of volatile components produced by Trichoderma and Gliocladium isolates reveal that the fungal BCAs produced considerable amount of volatile antibiotic compounds in vitro. Production of antibiotics and degree of suppression of both mycelial and sclerotial growth of pathogen varied with type and age of the antagonist. Gliocladium isolate JPG4 at different ages inhibited the sclerotial growth of the pathogen completely within 5 days. Gliocladium JPG1 and Trichoderma JPT9 isolates significantly inhibited sclerotial growth of M. phaseolina at different ages.